Union Strategies, National Institutions and the Use of Temporary Labour in Italian and US Plants. (18th May 2015) - Pulignano, Valeria; Signoretti, Andrea
Abstract: This article analyses variation in the use of temporary labour based on a comparison of two plants of the same US automotive multinational corporation, one in Italy and the other in the United States. We argue that differences in the use of temporary labour are explained by union capacities to make trade‐offs between alternative forms of flexibility as well as trade‐offs in the protection of internal and external groups of workers. Union capacity is dependent on the availability of power resources within different national institutional environments. These resources are shown to influence not only the ways in which temporary workers are used but also bargaining outcomes — including employment conditions — benefiting them.